The Challenges of Pre-Service Teachers in the New Normal Set up of Field Study Amidst COVID-19 Pandemic: A Case Study - Marquez, Bryan Jacob; Andrada, Joven; Baldomar, Trixie; Cunanan, Geri Mae; Ortiguero, Freddie; Padre, Michelle; Rey, Hannah (International Journal of Research in STEM Education, 2023)
The pandemic had a huge impact on many things and situations, particularly the new normal. The researchers decided that field study of pre-service teachers is one of them because no one has ever taken the course under the new COVID-19 setup. The researchers aim to inform their readers about how the COVID-19 pandemic challenge will affect every pre-service teacher in the new set-up of education through online learning. Purposive homogenous sampling was used to choose 12 students from Rizal Technological University-Boni and Pasig Campuses. Researchers chose typical students, non-workers, and university scholars as participants. Age, gender, and geography vary among participants. Researchers used interviews and supported by an interview script to gather replies. Pandemic-related preparations have been taken. Thematic analysis is used to understand pre-service teachers' challenges in the new field study setup. Pre-service teachers face challenges in this setting, according to the research most are struggling because of the rapid move from traditional classes to the new typical format, causing unpreparedness and lack of expertise when they face more complex situations. In addition, slow internet and a lack of resources make it difficult to attend classes and meet prerequisites. Some have many restrictions, especially on classroom monitoring because of the pandemic. The findings imply that the study's premise is significant and relevant in today's environment, especially for individuals pursuing an education degree and becoming pre-service teachers. Pre-service teachers face new obstacles in the new normal.